Analisis Kebutuhan Mata Kuliah Bahasa Inggris Bagi Mahasiswa Di Fakultas Kelautan Dan Perikanan - Ni Ketut Sri Rahayuni (Politeknik Kampar, 2023)
Carrying out a needs analysis can help find out whether the program fits the learner's goals and objectives for learning a language and at the same time can be used to help improve various components of the program that are more oriented to the learner's needs. Needs analysis can also help in evaluating existing programs and if deficiencies are found it can help in determining the need to introduce changes that may suit the needs of learners.